The Future of Archives Learning with Technology: Exploring the Potential of Virtual Labs - Ernawati, Yeni Purneni Susi; Asrowi; Sukmawati, Fatma (Universitas Pendidikan Ganesha, 2024)
The use of interactive media in vocational schools is extremely important for improving learning effectiveness. In today's digital era, interactive media can inspire students, improve understanding, and provide them with technology-driven skills that are relevant for the future. Therefore, the aim of this study is to analyze the potential and opportunities for creating an interactive multimedia platform called Virtual Lab (V-Lab) for archival learning in vocational schools. This research used a mixed method approach, with a sample size of 2 teachers and 103 students. The data collected includes both qualitative and quantitative data. Qualitative data was gathered through observation and interviews, using observation sheets and interview guidelines as tools. Quantitative data was collected through non-test techniques, specifically questionnaires, followed by data analysis using questionnaires as tools. The research data analyzed descriptively through interactive analysis, which involves data collection, data reduction, data presentation, and drawing conclusions. The findings of this research showed that teachers mainly used ICT-based media, such as presentation slides, YouTube, and the internet during the learning process. Additionally, a large majority of students expressed their agreement towards the development of Virtual Lab-based interactive multimedia, as it enhanced their practical learning experiences. This initiative and desire must be realized in order to promote innovative and dynamic learning implementation. The outcomes of this research could serve as a basis for the development of learning innovations, particularly in terms of interactive learning media that incorporate digital elements, which could be accessed through smartphones and support learning activities in vocational schools.